The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.jacc.2015.10.093
|View full text |Cite
|
Sign up to set email alerts
|

Biallelic Truncating Mutations in ALPK3 Cause Severe Pediatric Cardiomyopathy

Abstract: Biallelic truncating mutations in the newly identified gene ALPK3 give rise to severe, early-onset cardiomyopathy in humans. Our findings highlight the importance of transcription factor pathways in the molecular mechanisms underlying human cardiomyopathies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
83
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(93 citation statements)
references
References 28 publications
10
83
0
Order By: Relevance
“…While much of the existing literature on the clinical experience using genomic sequencing in inherited cardiomyopathies consists of case reports describing the use of WES for gene discovery in a proband 39 or small collections of families with severe complex cardiomyopathies of unknown etiology, 27,40 data from small cardiomyopathy cohorts have also been reported. Seidelmann et al 41 reported their experience with WES in a variety of inherited cardiovascular conditions, including HCM.…”
Section: Discussionmentioning
confidence: 99%
“…While much of the existing literature on the clinical experience using genomic sequencing in inherited cardiomyopathies consists of case reports describing the use of WES for gene discovery in a proband 39 or small collections of families with severe complex cardiomyopathies of unknown etiology, 27,40 data from small cardiomyopathy cohorts have also been reported. Seidelmann et al 41 reported their experience with WES in a variety of inherited cardiovascular conditions, including HCM.…”
Section: Discussionmentioning
confidence: 99%
“…For example, premature termination codons (PTC) in the ALPK3 gene were recently found in neonates who succumbed to precocious cardiomyopathy. 82 It may prove informative to generate similar alleles of Alpk3 in mice to understand the nature of this new genetic form of human cardiomyopathy.…”
Section: Two-component Crisprmentioning
confidence: 99%
“…In addition, exome sequencing will continue to disclose rare mutations associated with defects in the cardiovascular system that will be amenable for study in the mouse. 82 Since the desired edit will generally involve only one nucleotide substitution, single-strand oligonucleotide donors of 120–140 nucleotides length will be sufficient as HDR templates. A challenge in correcting or modeling a human variant in protein-coding sequence is the constrained sequence space for designing an optimal sgRNA; if the desired edit is too far removed from the DSB, integration of the edit may not occur or will do so inefficiently.…”
Section: Three Component Crisprmentioning
confidence: 99%
“…Intercalated discs comprise adherens junctions, gap junctions, and desmosomes, which are collectively important for electromechanical coupling. Remodeling of intercellular junctions is a well-studied area of heart disease and heart failure; the absence of desmosomal proteins at the cell membrane, as shown by Almomani et al (3) with reduced plakoglobin, has been previously reported in arrhythmogenic cardiomyopathy (AC) (6). Plakoglobin, in particular, plays a dual role as both a structural protein of the desmosome and a signaling molecule in the Wnt/β-catenin pathway.…”
mentioning
confidence: 98%
“…In this issue of the Journal , Almomani et al (3) report ALPK3 as a novel gene in human pediatric cardiomyopathy. Using a combination of homozygosity mapping, whole exome sequencing, and candidate gene screening, the group identified homozygous premature stop codon mutations in ALPK3 and, from immunohistological observations of heart tissue, suggest potential mechanisms for further exploration.…”
mentioning
confidence: 99%